Analisa Kinerja Protokol Routing Destination Sequenced Distance Vector Di Jaringan VANET - Muhamad Yusuf; Ramdhani Syahputra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Vehicular network is a network where vehicles communicate via an ad-hoc network system that runs based on certain ad-hoc routing protocols. A vehicle ad-hoc network consists of two communication parts known as vehicle-to-vehicle communication and vehicle-to-infrastructure communication. Even though the roads have become very congested with many vehicles, controlling vehicle movement has become an urgent need. Automatic traffic control, critical moment notifications, post-accident notifications, correct route selection become very important and these can be implemented using vehicle ad-hoc network systems. For good communication between vehicles, vehicle ad-hoc networks use several protocols. One of the problems faced by VANET is routing. Routing in VANETs can perform challenging tasks due to high mobility, network topology interference, and path selection processes. DSDV is one of the routing used in VANET and simulations were carried out with NS2 to obtain DSDV routing performance in the VANET network based on quality of service with scenarios of 25 and 33 nodes. DSDV routing was chosen because it has the best performance in its class. From the simulation results, the end to end delay for 25 nodes is 22.22 and 33 nodes is 24.07, the packet drop obtained for 25 nodes is 0.85, and 33 nodes is 0.80. Furthermore, the throughput value obtained in the simulation for 25 nodes is 274.19 and 33 nodes 351.12, then the packet delivery ratio for 25 nodes is 2990, and 33 nodes is 4888